Elementary Knowledge and Attitude of MBBS Students towards Medico Legal Autopsy - Shrestha, Niranjan; Katwal, Barsika; Limbu, Bhumikala (Nepal Medical College Journal, 2025)
Autopsy is an important investigating procedure to establish the cause of death. As rules regulated by Nepal Medical Council, a medical student of all medical colleges in Nepal can witness medico legal autopsies in the third year of MBBS. The main objective of this study is to investigate the general attitude of medical students of 3rd, years MBBS towards medico-legal autopsy/Clinical autopsy. In September 2021, a descriptive and cross sectional study was performed in Nepal medical college teaching hospital among 90 students. In this study prepared questioner with several questions were given to the participated students about the knowledge of autopsy and its procedure. These questions also aimed to know the attitude and perception towards postmortem examination. Later, the results were analyzed in detail and were represented in frequency. About 97.78% students agreed that medico-legal postmortem examination is mandatory in all unnatural and suspicious deaths to know the cause of death. Majority 87.78% of the students said they should watch more postmortem examination. None of the students 100% said post mortem examination should be removed from medical education. Nearly 95.56% students said that they should actively participate in performing autopsies. Maximum number of students i.e.52.22% prefer virtual autopsy. About 80% of students said that taking out viscera is necessary for histo-pathological examinations and toxicological analysis in cases of medico legal autopsies.94.44% students have opinion for not wishing specialization in Forensic Medicine due to interest in other specialties. Medical students must be provided by all the educational and necessary facilities to encourage in this field of forensic medicine.